DAMPAK NEGATIF MEDIA SOSIAL YOUTUBE TERHADAP PERILAKU PESERTA DIDIK - Made Saihu (STIT AL-AMIN KREO TANGERANG, 2021)
This research was conducted because it saw the many negative impacts caused by YouTube social media. Basically, innovation and creation were created to make it easier for humans to carry out their daily activities. However, if this is done in a way that is not wise, then slowly the goal will not be achieved, instead it will have an adverse impact on its users. The purpose of this study was to determine the negative impact of YouTube social media on students. This research is classified as a case study research with qualitative descriptive analysis techniques by collecting data or materials related to the theme of the discussion and the problems taken from the sources found in the research location. The negative impacts of YouTube social media include: First, the decline in student enthusiasm for learning. The two are fighting with friends. The third said no good. The four interrupt in class